Apoptosis Inducing Effect of Plumbagin on Colonic Cancer Cells Depends on Expression of COX-2 - Subramaniya, Bharathi Raja (Public Library of Science, 2011)
Plumbagin, a quinonoid found in the plants of the Plumbaginaceae, possesses medicinal properties. In this study we investigated the anti-proliferative and apoptotic activity of plumbagin by using two human colonic cancer cell lines, HT29 and HCT15. IC50 of Plumbagin for HCT15 and HT29 cells (22.5 µM and 62.5 µM, respectively) were significantly different. To study the response of cancer cells during treatment strategies, cells were treated with two different concentrations, 15 µM, 30 µM for HCT15 and 50 µM, 75 µM for HT29 cells. Though activation of NFκB, Caspases-3, elevated levels of TNF-α, cytosolic Cytochrome C were seen in both HCT15 cells HT29 treated with plumbagin, aberrant apoptosis with decreased level of pEGFR, pAkt, pGsk-3β, PCNA and Cyclin D1was observed only in 15 µM and 30 µM plumbagin treated HCT15 and 75 µM plumbagin treated HT29 cells. This suggests that plumbagin induces apoptosis in both HCT15 cells and HT29 treated, whereas, proliferation was inhibited only in 15 µM and 30 µM plumbagin treated HCT15 and 75 µM plumbagin treated HT29 cells, but not in 50 µM plumbagin treated HT29 cells. Expression of COX-2 was decreased in 75 µM plumbagin treated HT29 cells when compared to 50 µM plumbagin treated HT29 cells, whereas HCT15 cells lack COX. Hence the observed resistance to induction of apoptosis in 50 µM plumbagin treated HT29 cells are attributed to the expression of COX-2. In conclusion, plumbagin induces apoptosis in colonic cancer cells through TNF-α mediated pathway depending on expression of COX-2 expression.